Mutation and linkage disequilibrium analysis in genetic counselling of Spanish cystic fibrosis families. Issue 11 (November 1991) - Casals, T; Nunes, V; Lázaro, C; Giménez, F J; Girbau, E; Volpini, V; Estivill, X
Abstract : We have analysed haplotypes for four DNA polymorphisms, closely linked to the cystic fibrosis (CF) gene, in 82 Spanish families, in which the CF probands are either homozygous for non-delta F508 mutations or heterozygous for the delta F508 deletion and other CF mutations. The analysis provides genetic data for a new polymorphism for the closely linked marker pKM.19, which is very strongly associated with CF. Haplotypes generated with the four marker loci are also in strong disequilibrium with the non-delta F508 CF chromosomes. The data reported here are useful in 1 in 4 risk pregnancies of parents who have no living affected child, and when counselling close relatives of CF families who are negative for the major CF mutation. The data presented are useful in our population, in which the majority of CF mutations, apart from the delta F508 deletion, are uncommon. For other populations in which mutation heterogeneity is also very high, it still might be more feasible to use RFLPs for diagnostic purposes, when analysis for common mutations is negative and DNA is available from the index patient. The experience presented here provides a model for these population groups who in turn should obtain their own haplotype data. In addition, the model system for genetic counselling presented here might also be useful for other genetic disorders.